Mystery : an Alex Delaware novel - Kellerman, Jonathan (London : Headline, 2011)
Psychologist Alex Delaware and his girlfriend Robin are making a farewell visit to an LA hotel bar when one patron in particular grabs their attention -- a beautiful but aloof young woman dressed all in white. Two days later, Alex is called in on a murder case and is shocked when he recognizes the victim as the woman in white
Keywords: Delaware, Alex (Fictitious character) -- Fiction; Sturgis, Milo (Fictitious character) -- Fiction; Forensic psychologists -- Fiction; Police -- California -- Los Angeles -- Fiction